Congenital dystrophic epidermolysis bullosa (DEB) in Sprague Dawley rats: a case series. Issue 2 (24th February 2016) - Eden, Kristin B.; Peterson, Ashley; Payne, Harold R.; Corapi, Wayne V.; Mansell, Joanne; Hoffman, Aline Rodrigues
Abstract : Background: Epidermolysis bullosa is a rare skin disease caused by defects in the basement membrane and/or other dermoepidermal junction components. Hypothesis/Objectives: We describe a series of spontaneous cases of dystrophic epidermolysis bullosa (DEB) in a colony of Sprague Dawley rats investigated with histopathology, transmission electron microscopy (TEM) and inheritance pattern. Animals: Four, 4‐day‐old pups from a litter of Sprague Dawley rats developed blistering, haemorrhagic skin lesions and were euthanized. Age‐matched controls from the same litter were normal. Several months later two more litters presented with identical findings. All three litters had the same sire, suggesting a genetic component. Methods: Skin from affected and control animals was evaluated histologically and with TEM. Unaffected sibling pairs from affected litters were bred in order to potentially reproduce the disease and determine the mode of inheritance. Results: Histologically, there was significant dermoepidermal clefting below the basement membrane with variable amounts of haemorrhage and cellular debris within the clefts. Ultrastructurally, clefting occurred below the basement membrane with an intact lamina densa and normal hemidesmosomes. Anchoring filaments were strikingly absent. Litters produced from phenotypically unaffected sibling pairs resulted in a total of four more litters with approximately a quarter of pups affected. Conclusions and clinical importance: Based on the gross lesions, histopathological features and TEM determination of separation below the lamina densa and lack of normal anchoring fibrils, these cases are most consistent with DEB. This is the first report of naturally occurring, localized and reproducible recessive DEB in Sprague Dawley rats. Abstract : Background – Epidermolysis bullosa is a rare skin disease caused by defects in the basement membrane and/or other dermoepidermal junction components.Hypothesis/Objectives – We describe a series of spontaneous cases of dystrophic epidermolysis bullosa (DEB) in a colony of Sprague Dawley rats investigated with histopathology, transmission electron microscopy (TEM) and inheritance pattern.Conclusions and clinical importance – Based on the gross lesions, histopathologic features and TEM determination of separation below the lamina densa and lack of normal anchoring fibrils, these cases are most consistent with DEB. This is the first report of naturally occurring, localized and reproducible recessive DEB in Sprague Dawley rats.